Korzystanie z pamięci organizacji w procesach ograniczania środowiskowej uciążliwości przedsiębiorstwa - Kobyłko, Grzegorz (Organizational Memory for Limiting the Environmental Pressure of the Enterprise, 2005)
The article systematizes the relation between knowledge about environment and the rational process of limiting the environmental pressure of enterprise. The author shows the meaning of organizational memory, which has fundamental importance for correct cognitive processes. The author proposes to widen this notion recognising the memory of participants of the process to be the basis of the rational cognition of reality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 82-91